Biblical Allusion between Parallel and Contrast in John Steinbeck's To A God Unknown: The Protagonist as a Study Case - Hadi Salih Sultan; Fidan Kassim Salladin (PROSPECTIVE RESEARCHES, 2023)
The present study aims at shedding lights on the areas of allusion between the protagonist of Steinbeck's To A God Unknown and Joseph the prophet. It is divided into an introduction and two other sections. The introduction tackles some definitions of allusion and its sources. The definitions are separated into two kinds according to their generality for every definition serves a certain aspects of the subject. It also concentrates on the role of the reader in participating in the creative process. He is also regarded as a second pole in the process. It also alludes to different sources of allusion and how this technique develops through ages. The second section is devoted to the parallel allusion between Joseph Wayne, the protagonist of the novel and the Biblical Joseph. It studies their birth, journeys and responsibilities which come to be almost parallel. The third section deals with the areas of contrast between the two characters especially those which concern faith and temptation. The conclusion summarizes the results of the paper.